Preliminary Study of Exercise Capacity in Post-acute Stroke Survivors - June-Kai Chen; Tien-Wen Chen; Chia-Hsin Chen; Mao-Hsiung Huang (Kaohsiung Journal of Medical Sciences, 2010)
The purpose of this study was to evaluate the feasibility and exercise capacity of cycle ergometry exercise testing and exercise performance in patients with post-acute stroke. Nineteen male patients (mean age, 62.7 ± 9.2 years) with a post stroke interval of 9.9 ± 2.0 days underwent symptom- limited cardiopulmonary exercise testing. Peak exercise capacity was measured by open-circuit spirometry during standard upright ergometer cycling. The mean peak oxygen uptake was 11.8 mL/kg/min, peak heart rate with age-predicted maximal heart rate was 67.9 ± 3.4%, and peak oxygen pulse was 7.5 mL/beat. The anaerobic threshold was achieved with a mean peak oxygen uptake of 73.4%. Mean peak minute ventilation was 42.1 L/min, and ventilatory reserve was 48.1 ± 16.8%. Our findings confirm that cycle ergometry exercise testing is feasible and exercise capacity is compromised in post-acute stroke survivors within 2 weeks after stroke. Respiratory impairments do not appear to contribute to the reduced exercise capacity post stroke.